Social media marketing impact on GARNIER brand promotion and customer awareness at WAVEMAKER Bangladesh - Tabassum, Rakshanda (BRAC Univeristy, 2018)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2018.